Coenzyme Q10 and pro-inflammatory markers in children with Down syndrome: clinical and biochemical aspects - Moushira E. Zaki; Hala T. El-Bassyouni; Angie M.S. Tosson; Eman Youness; Jihan Hussein (Elsevier, 2017)
Objective: Evidence of oxidative stress was reported in individuals with Down syndrome. There is a growing interest in the contribution of the immune system in Down syndrome. The aim of this study is to evaluate the coenzyme Q10 and selected pro-inflammatory markers such as interleukin 6 and tumor necrosis factor α in children with Down syndrome. Methods: Eighty-six children (5-8 years of age) were enrolled in this case-control study from two public institutions. At the time of sampling, the patients and controls suffered from no acute or chronic illnesses and received no therapies or supplements. The levels of interleukin 6, tumor necrosis factor α, coenzyme Q10, fasting blood glucose, and intelligence quotient were measured. Results: Forty-three young Down syndrome children and forty-three controls were included over a period of eight months (January-August 2014). Compared with the control group, the Down syndrome patients showed significant increase in interleukin 6 and tumor necrosis factor α (p = 0.002), while coenzyme Q10 was significantly decreased (p = 0.002). Also, body mass index and fasting blood glucose were significantly increased in patients. There was a significantly positive correlation between coenzyme Q10 and intelligence quotient levels, as well as between interleukin 6 and tumor necrosis factor α. Conclusion: Interleukin 6 and tumor necrosis factor α levels in young children with Down syndrome may be used as biomarkers reflecting the neurodegenerative process in them. Coenzyme Q10 might have a role as a good supplement in young children with Down syndrome to ameliorate the neurological symptoms. Resumo: Objetivo: Foram relatadas evidências de estresse oxidativo em indivíduos com a síndrome de Down. Há um interesse cada vez maior na contribuição do sistema imunológico na síndrome de Down. O objetivo deste estudo é avaliar a coenzima Q10 e marcadores pró-inflamatórios selecionados, como interleucina 6 e fator de necrose tumoral α, em crianças com a síndrome de Down. Métodos: 86 crianças (5-8 anos de idade) de duas instituições públicas foram inscritas neste estudo de caso-controle. No momento da amostragem, os pacientes e os controles não sofriam de nenhuma doença aguda ou crônica e não recebiam nenhuma terapia ou suplementos. Foram medidos os níveis de interleucina 6, fator de necrose tumoral α, coenzima Q10, glicemia de jejum e quociente de inteligência. Resultados: 43 crianças com síndrome de Down e 43 controles foram incluídos em um período de 8 meses (janeiro-agosto 2014). Em comparação ao grupo de controle, os pacientes com síndrome de Down mostraram aumento significativo na interleucina 6 e no fator de necrose tumoral α (p = 0,002), ao passo que a coenzima Q10 apresentou significativa redução (p = 0,002). Além disso, o índice de massa corporal e a glicemia de jejum eram significativamente maiores nos pacientes. Houve uma correlação significativamente positiva entre os níveis de coenzima Q10 e do quociente de inteligência, bem como entre a interleucina 6 e o fator de necrose tumoral α. Conclusão: Os níveis de interleucina 6 e fator de necrose tumoral α em crianças mais novas com síndrome de Down podem ser utilizados como biomarcadores, refletindo o processo neurodegenerativo neles. A coenzima Q10 pode ter um papel como bom suplemento em crianças com síndrome de Down para melhorar os sintomas neurológicos. Keywords: Coenzyme Q10, Down syndrome children, Interleukin 6, Oxidative stress, Tumor necrosis factor α, Palavras-chave: Coenzima Q10, Crianças com síndrome de Down, Interleucina 6, Estresse oxidativo, Fator de necrose tumoral α